Effects of weightlessness on the cardiovascular system: a systematic review and meta-analysis - Mendes Zambetta, Rafaella; Signini, Étore De Favari; Ocamoto, Gabriela Nagai; Catai, Aparecida Maria; Uliam, Nicoly Ribeiro; Santarnecchi, Emiliano; Russo, Thiago Luiz (Frontiers in Physiology, 2024)
The microgravity environment has a direct impact on the cardiovascular system due to the fluid shift and weightlessness that results in cardiac dysfunction, vascular remodeling, and altered cardiac autonomic modulation (CAM), deconditioning and poor performance on space activities, ultimately endangering the health of astronauts. Objective: This study aimed to identify the acute and chronic effects of microgravity and Earth analogues on cardiovascular anatomy and function and CAM. Methods: CINAHL, Cochrane Library, Scopus, Science Direct, PubMed, and Web of Science databases were searched. Outcomes were grouped into cardiovascular anatomic, functional, and autonomic alterations, and vascular remodeling. Studies were categorized as Spaceflight (SF), Chronic Simulation (CS), or Acute Simulation (AS) based on the weightlessness conditions. Meta-analysis was performed for the most frequent outcomes. Weightlessness and control groups were compared. Results: 62 articles were included with a total of 963 participants involved. The meta-analysis showed that heart rate increased in SF (Mean difference [MD] = 3.44; P = 0.01) and in CS (MD = 4.98; P < 0.0001), whereas cardiac output and stroke volume decreased in CS (MD = -0.49; P = 0.03; and MD = -12.95; P < 0.0001, respectively), and systolic arterial pressure decreased in AS (MD = -5.20; P = 0.03). According to the qualitative synthesis, jugular vein cross-sectional area (CSA) and volume were greater in all conditions, and SF had increased carotid artery CSA. Heart rate variability and baroreflex sensitivity, in general, decreased in SF and CS, whereas both increased in AS. Conclusion: This review indicates that weightlessness impairs the health of astronauts during and after spaceflight, similarly to the effects of aging and immobility, potentially increasing the risk of cardiovascular diseases.